Environmental gamma dose rate measurements using cadmium zinc telluride (CZT) detectors - Kreutzer, Sebastian; Martin, Loïc; Miallier, Didier; Mercier, Norbert (Geochronology, 2025)
The accurate and precise determination of the environmental dose rate is pivotal in every trapped-charge dating study. The environmental γ dose rate component can be determined from radionuclide concentrations using conversion factors or directly measured in situ with passive or active detectors. In-field measurements with an active detector are usually inexpensive and straightforward to achieve with adequate equipment and calibration. However, despite the rather widespread use of portable NaI or LaBr3 scintillator detectors, there is a lack of research on the performance and practicality of portable alternative detectors in dating studies, particularly in light of newer developments in the semi-conductor industry. Here, we present our experience with two small portable semi-conductor detectors housing cadmium zinc telluride (CZT) crystals. Given their small volume and low power consumption, we argue they present attractive alternatives for γ dose rate measurements in dating studies. Despite high relative detection efficiency, their small volume may pose different challenges, resulting in impractical measurements in routine studies, and therefore need investigation. In our study, we simulated the particle interaction of the CZT crystal with GEANT4 in different sediment matrices to quantify the energy threshold in the spectrum above which the count/energy count rate correlates with the environmental gamma dose rate irrespective of the origin of the γ photons. We compared these findings with experimentally derived cumulative spectra and dose rate calibration curves constructed from reference sites in France and Germany, which yielded unrealistically low threshold values, likely due to the limited variability of the investigated sites. We additionally report negligible equipment background and required minimal measurement time of only 20 min in typical environments. Cross-checking our calibration on a homogeneous loess deposit near Heidelberg confirmed the setting and assumed performance through a nearly identical γ dose rate of 1107 ± 65 µGy a−1 (CZT) to 1105 ± 11 µGy a−1 (laboratory). The outcome of our study gives credit to our threshold definition. It validates the similarity of the two investigated probes, which may make it straightforward for other laboratories to implement the technique effortlessly. Finally, the implementation of CZT detectors has the potential to streamline fieldwork and enhance the accuracy and precision of trapped-charge dating-based chronologies.